Novel phenotype of achondroplasia due to biallelic FGFR3 pathogenic variants. Issue 7 (16th July 2018) - Chang, Irene J.; Sun, Angela; Bouchard, Maryse L.; Kamps, Shawn E.; Hale, Susan; Done, Stephen; Goldberg, Michael J.; Glass, Ian A.
Abstract : Pathogenic variants in the fibroblast growth factor receptor 3 ( FGFR3 ) gene are responsible for a broad spectrum of skeletal dysplasias, including achondroplasia (ACH). The classic phenotype of ACH is caused by two highly prevalent mutations, c.1138G > A and c.1138G > C (p.Gly380Arg). In the homozygous state, these variant results in a severe skeletal dysplasia, neurologic deficits, and early demise from respiratory insufficiency. Although homozygous biallelic mutations have been reported in patients with ACH in combination with hypochondroplasia or other dominant skeletal dysplasias, thus far, no cases of heterozygous biallelic pathogenic ACH‐related variants in FGFR3 have been reported. We describe a novel phenotype of an infant with two ACH‐related mutations in FGFR3, p.Gly380Arg and p.Ser344Cys. Discordant features from classic ACH include atypical radiographic findings, severe obstructive sleep apnea, and focal, migrating seizures. We also report the long‐term clinical course of her father, who harbors the p.Ser344Cys mutation that has only been reported once previously in a Japanese patient. The phenotype of heterozygous biallelic mutations in FGFR3 associated with ACH is variable, underscoring the importance of recognition and accurate diagnosis to ensure appropriate management.